Comprehensive analysis of the expression patterns and function of the FTO–LINE1 axis in yak tissues and muscle satellite cells - Ma, Zongliang; Chai, Zhixin; Yang, Huan; Zhang, Xiangfei; Zhao, Hongwen; Luo, Xiaolin; Zhong, Jincheng; Wu, Zhijuan (Frontiers in Veterinary Science, 2024)
BackgroundThe long interspersed nuclear element 1 (LINE1) retrotransposon has been identified as a specific substrate for fat mass and obesity-related gene (FTO), which facilitates the removal of N6-methyladenosine modifications from its targeted RNAs.MethodsThis study examined the dynamic interaction between FTO and LINE1 in yak tissues and muscle satellite cells, utilizing RT-qPCR, RNA immunoprecipitation (RIP), immunofluorescence staining, and techniques involving overexpression and interference of FTO and LINE1 to elucidate the relationship between FTO and LINE1 in yak tissues and muscle satellite cells.ResultsCloning and analysis of the FTO coding sequence in Jiulong yak revealed a conserved protein structure across various Bos breeds, with notable homology observed with domestic yak, domestic cattle, and Java bison. Comprehensive examination of FTO and LINE1 gene expression patterns in Jiulong yaks revealed consistent trends across tissues in both sexes. FTO mRNA levels were markedly elevated in the heart and kidney, while LINE1 RNA was predominantly expressed in the heart. Immunoprecipitation confirmed the direct interaction between the FTO protein and LINE1 RNA in yak tissues and muscle satellite cells. The FTO–LINE1 axis was confirmed by a significant decrease in LINE1 RNA enrichment following its expression interference in yak muscle satellite cells. Overexpression of FTO substantially reduced the expression of recombinant myogenic factor 5 (MYF5). However, FTO interference had no discernible effect on MYF5 and myoblast determination protein 1 (MYOD1) mRNA levels. Immunofluorescence analysis revealed no alterations in Ki-67 protein expression following FTO interference or overexpression. However, phalloidin staining demonstrated enhancement in the myotube fusion rate of yak muscle satellite cells upon LINE1 interference.ConclusionThis comprehensive mapping of the FTO and LINE1 mRNA expression patterns establishes a direct interaction between the FTO protein and LINE1 RNA in yak. The findings suggest that FTO overexpression promotes muscle satellite cells differentiation, whereas LINE1 negatively regulates myotube fusion. The study provides fundamental insights into the role of the FTO–LINE1 axis in determining the fate of muscle satellite cells in yak, laying a solid theoretical foundation for future investigations.